2019
DOI: 10.1097/corr.0000000000000757
|View full text |Cite
|
Sign up to set email alerts
|

Polytrauma and High-energy Injury Mechanisms are Associated with Worse Patient-reported Outcomes After Distal Radius Fractures

Abstract: Background Patient-reported outcomes (PROs) are increasingly relevant when evaluating the treatment of orthopaedic injuries. Little is known about how PROs may vary in the setting of polytrauma or secondary to high-energy injury mechanisms, even for common injuries such as distal radius fractures. Questions/purposes (1) Are polytrauma and high-energy injury mechanisms associated with poorer long-term PROs (EuroQol Five Dimension Three Levels [EQ-5D-3L] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 36 publications
0
6
2
2
Order By: Relevance
“…This precious finding may have influenced our Group PT-U and may, therefore, have led to the lack of significance, although the multivariable regression analyses could not confirm a correlation between EQ-VAS and ISS, age, gender or TBI. Contrary to the results of this study, van der Vliet et al [36] investigated the impact of injury severity and injury distribution on the outcome of upper extremity fracture and found that the EQ-5D is not affected by polytrauma in extraarticular fractures. Furthermore, they showed that the quick DASH is affected by increasing trauma energy [36].…”
Section: Patient-reported Outcomecontrasting
confidence: 88%
See 1 more Smart Citation
“…This precious finding may have influenced our Group PT-U and may, therefore, have led to the lack of significance, although the multivariable regression analyses could not confirm a correlation between EQ-VAS and ISS, age, gender or TBI. Contrary to the results of this study, van der Vliet et al [36] investigated the impact of injury severity and injury distribution on the outcome of upper extremity fracture and found that the EQ-5D is not affected by polytrauma in extraarticular fractures. Furthermore, they showed that the quick DASH is affected by increasing trauma energy [36].…”
Section: Patient-reported Outcomecontrasting
confidence: 88%
“…Contrary to the results of this study, van der Vliet et al [36] investigated the impact of injury severity and injury distribution on the outcome of upper extremity fracture and found that the EQ-5D is not affected by polytrauma in extraarticular fractures. Furthermore, they showed that the quick DASH is affected by increasing trauma energy [36]. Since only intraarticular PHF were analyzed in this cohort, the results might not be comparable.…”
Section: Patient-reported Outcomecontrasting
confidence: 88%
“…Nach einem Aufprall bilden sich im Bereich des Sicherheitsgurts Hämatome. Hämatome außerhalb des Sicherheitsgurts sind Hinweise auf ein erhöhtes Risiko erheblicher Verletzungen im Bauch-, Gefäß-und Wirbelsäulenbereich [2,3,6,7,[11][12][13][14].…”
Section: Merkeunclassified
“…Insassen, die bei einem Verkehrsunfall aus dem Fahrzeug geschleudert werden, haben beim Verlassen des Fahrzeugs die gleiche Geschwindigkeit wie das Fahrzeug. Dies führt zu einem großen Impuls des Insassen, der beim Aufprall auf den Boden oder beim Anprall auf ein Hindernis nicht übertragen werden kann, sodass es zu schweren bis schwersten Verletzungen kommt [2,3,6,7].…”
Section: Der Patient Wurde Aus Einem Fahrzeug Geschleudertunclassified
“…Pathophysiologically, patients with polytrauma are at elevated risk for respiratory and multi-organ failure, 29,30 coagulopathy, 5,31 hypotension, 31 systemic inflammation, 32 and other predictors of mortality and poor outcome, in addition to delayed return to work 6 and financial burden from hospitalization. 4 Patients with polytrauma by definition have sustained additional injuries, any of which may impair long-term function, 33 confer pain and disability, 34 and therefore confound global measures of functional recovery such as the GOSE. Additionally, although we did not analyze the incidence of non-neurosurgical operative interventions, patients with polytrauma are more likely to require additional surgeries that in turn may prolong their hospitalization, rehabilitation, and recovery.…”
Section: Fig 2 (Ab) Distribution Of Gose At 3 and 6 Months Between Tbi Patients With And Without Polytraumamentioning
confidence: 99%